Unveiling Knowledge, Attitude and Practice on Carbonated Drinks Intake Among Male and Female Young Adults in Pekan, Pahang - Mohamad Zailani, Nurfarzana; Hamirudin, Aliza Haslinda (International Journal of Allied Health Sciences, 2024)
Background: Consumption of carbonated soft drinks has increased over the years, contributing to health issues such as obesity and non-communicable diseases (NCDs) particularly diabetes. Various factors influencing young adults to consume carbonated drinks, but research remains limited. This study aimed at assessing knowledge, attitude and practice (KAP) on carbonated drinks consumption among young adults in Pekan, Pahang specifically comparison between males and females. Methods: A cross-sectional study was conducted among a total of 94 respondents (n=47 males, n=47 females) aged 18 to 35 years old. The KAP questionnaires were distributed across residential areas in Pekan, Pahang. Statistically significant was set at p<0.05 Results: No significant difference was detected in knowledge score between males and females (p=0.831) indicating there was no difference among males and females related to knowledge and understanding level on carbonated drinks. Meanwhile, significant differences were identified for both attitude (p=0.049) and practice (p=0.032) score in percentage between males and females. Males exhibited greater attitude on consumption and higher practice on carbonated drinks intake compared to females. Conclusion: Findings indicate similar level of knowledge between gender. Males had negative attitude and greater practice on carbonated drinks intake than females. Thus, it is imperative for targeted strategies according to genders in nutrition education and health promotion strategies. Enhancing awareness on adverse health effects related to carbonated drinks intake could improve knowledge and further prevent rising rate of NCDs.